2022
DOI: 10.3389/fonc.2022.833814
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Ferroptosis by Ophiopogonin-B Through Regulating the Gene Signature AURKA in NSCLC

Abstract: Ferroptosis is a new type of iron-dependent programmed cell death. In recent years, its role in the diagnosis and treatment of multiple tumors, including non-small cell lung cancer (NSCLC), has been continuously observed. The relationship between the ferroptosis-related genes and the prognosis of patients with NSCLC needs to be clarified. In this study, The Cancer Genome Atlas (TCGA) and the Gene Expression Synthesis database (Gene Expression Omnibus, GEO) were used to build a model of ferroptosis-related diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…2C), dorsomorphin (36) (AMPK inhibitor, Supplemental Fig. 2D), alisertib (37, 38) (Aurora kinase A inhibitor, Supplemental Fig. 2E), verdinexor and leptomycin B (39) (XPO1/CRM1 inhibitors, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…2C), dorsomorphin (36) (AMPK inhibitor, Supplemental Fig. 2D), alisertib (37, 38) (Aurora kinase A inhibitor, Supplemental Fig. 2E), verdinexor and leptomycin B (39) (XPO1/CRM1 inhibitors, Supplemental Fig.…”
Section: Resultsmentioning
confidence: 99%
“…However, there are few studies on the ferroptosis role and mechanism of AURKA. Li et al revealed that AURKA was a negative regulator for ferroptosis in NSCLC [ 36 ]. Zhao et al demonstrated that AURKA was a ferroptosis-related gene associated with worse survival outcomes in ES [ 37 ], but they did not further explore the specific mechanisms by which AURKA regulated ferroptosis in ES.…”
Section: Discussionmentioning
confidence: 99%
“…Very recently, Li et al ( 2022c ) conducted a bioinformatic analysis aimed at identifying ferroptosis-related genes and prognosis in NSCLC patients. The study brought to light a 12-gene signature where AURKA , the Aurora kinase A encoding gene, was reported to act as a negative regulator of ferroptosis.…”
Section: Natural Compounds As Ferroptosis Inducersmentioning
confidence: 99%